Penggunaan Quipper dalam Pembelajaran di Masa Pandemi pada Pembelajaran Kimia - Suparman, Yayan (LPPM Universitas Bina Bangsa, 2022)
The research method in this research is qualitative with a descriptive approach. This research was conducted on students of class XI IPA 1 to XI IPA 4 with a total of 144 students. Respondents who were interviewed were students of class XI to get an overview of online learning. Distance learning is a program for organizing online learning classes to reach a massive and broad target group. Through the network, learning can be held massively with unlimited participants. Online learning can be an alternative way for students to study well in the midst of the Covid-19 pandemic, it can also be an effort to break the chain of the spread of Covid-19